A Set of Rules for Constructing Gender-Based Personality Typesâ Composition for Software Programmer - Gilal, A.R. (Springer Verlag, 2019)
The current era has been declared as technological era where both profit and no-profit organisations rely solely on software to cope with myriad issues they typically face. The growing demand for software has equally placed challenging tasks on workplaces to produce quality and reliable software. Unfortunately, software development industries have drastically failed to produce software in due time or even if software is produced in time but it fails to yield the desired results. Keeping this problem in view, this study tried to address this problem by offering team composition model lucrative for software development. For instance, Personality types, especially Introvert (I) and Extrovert (E) traits, of team members of software development are explored with gender diversity with a key focus on the programmer role. Moreover, descriptive and predictive approaches were applied to gain the hidden facts from data. The data of this study was taken from both academia and industry to establish the generalizability in the findings. Additionally, different personality traits composition was set based on gender which was not studied in previous studies. The findings of this research suggest that male-programmer should be composed of E trait of personality and, whereas female-programmer should be I. The overall findings contribute to serve the cause of software development team and also contribute to the existing literature on software development and its team composition. Â© Springer Nature Singapore Pte Ltd. 2019.